Management of Nonrelaxing Pelvic Floor Dysfunction and Pain: Identifying the Gaps [A111]. (May 2022) - Young, Riley; Cope, Adela; Green, Isabel
Abstract : INTRODUCTION: Nonrelaxing pelvic floor dysfunction (PFD) is a condition characterized by tension of the pelvic floor musculature, often resulting in pelvic pain. The objective of this study was to review patient-reported pain outcomes following treatment of nonrelaxing pelvic floor dysfunction to identify gaps in current evidence. METHODS: A systematic review of the following databases from inception to July 2020 was performed: Ovid MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus. Two authors reviewed titles and abstracts for relevance, and full articles were obtained and evaluated for inclusion. Studies were included if they assess interventions for nonrelaxing PFD characterized by pelvic pain. The third author was consulted in instances of disagreement. RESULTS: Of the 1, 184 abstracts identified and reviewed, 36 full text articles were reviewed. Treatments for nonrelaxing PFD included biofeedback, botulinum toxin injections, electrical stimulation, intravaginal diazepam, massage, osteopathy, psychiatric interview, physical therapy, sacral nerve stimulation, trigger point injection, and combined therapies. Nineteen studies assessed the effectiveness of treatment based on patient reported pain outcomes. All studies demonstrated an improvement in pelvic pain. Several limitations were identified including varied pre-treatment diagnostic evaluation, small sample size, retrospective and single arm design, heterogeneity in treatment administration within and between studies, lack of standardized pain assessments, and limited long term outcome data. CONCLUSION: Nonrelaxing PFD is a debilitating condition. There is a paucity of high-quality clinical trials evaluating the effectiveness of pelvic floor muscle dysfunction treatments. Although preliminary studies support multi-modal treatment options, robust trials assessing patient-centered outcomes are necessary.